Navigator programme for hospitalised adults experiencing homelessness: protocol for a pragmatic randomised controlled trial. Issue 12 (14th December 2022) - Liu, Michael; Pridham, Katherine Francombe; Jenkinson, Jesse; Nisenbaum, Rosane; Richard, Lucie; Pedersen, Cheryl; Brown, Rebecca; Virani, Sareeha; Ellerington, Fred; Ranieri, Alyssa; Dada, Oluwagbenga; To, Matthew; et al.
Abstract : Introduction: People experiencing homelessness suffer from poor outcomes after hospitalisation due to systemic barriers to care, suboptimal transitions of care, and intersecting health and social burdens. Case management programmes have been shown to improve housing stability, but their effects on broad posthospital outcomes in this population have not been rigorously evaluated. The Navigator Programme is a Critical Time Intervention case management programme that was developed to help homeless patients with their postdischarge needs and to link them with community-based health and social services. This randomised controlled trial examines the impact of the Navigator Programme on posthospital outcomes among adults experiencing homelessness. Methods and analysis: This is a pragmatic randomised controlled trial testing the effectiveness of the Navigator Programme at an urban academic teaching hospital and an urban community teaching hospital in Toronto, Canada. Six hundred and forty adults experiencing homelessness who are admitted to the hospital will be randomised to receive support from a Homeless Outreach Counsellor for 90 days after hospital discharge or to usual care. The primary outcome is follow-up with a primary care provider (physician or nurse practitioner) within 14 days of hospital discharge. Secondary outcomes include postdischarge mortality or readmission, number of days in hospital, number of emergency department visits, self-reported care transition quality, and difficulties meeting subsistence needs. Quantitative outcomes are being collected over a 180-day period through linked patient-reported and administrative health data. A parallel mixed-methods process evaluation will be conducted to explore intervention context, implementation and mechanisms of impact. Ethics and dissemination: Ethics approval was obtained from the Unity Health Toronto Research Ethics Board. Participants will be required to provide written informed consent. Results of the main trial and process evaluation will be reported in peer-reviewed journals and shared with hospital leadership, community partners and policy makers. Trial registration number: NCT04961762 .